A pioneering experience in Brazil: the creation of a support network for alcohol and drug dependent physicians. A preliminary report - Palhares-Alves,Hamer Nastasy (2007)
OBJECTIVE: The objectives of this study are to present the creation and operation of a support network to help physicians in Brazil, describe the socio-demographic profile, and investigate the prevalence of mental disorders and chemical dependence among physicians seeking treatment. METHOD: Semi-structured interviews using ICD-10 criteria were conducted to obtain data regarding alcohol/drug dependence, and psychiatric comorbidity. Socio-demographic and occupational characteristics were obtained. RESULTS: 247 patients made contact and 192 attended the first evaluation visit. Of those, 158 were male, and most (55%) were married. The mean age was 42.4 ± 11.1 years. The reasons for seeking treatment were: comorbidity between mental disorders and chemical dependence (67.7%); chemical dependence (20.8%); mental disorders (7.8%); and burnout (4.2%). The mean interval between the detection of the problem and seeking treatment was 7.5 years. Factors associated with the severity of the problem included unemployment (21.6%), difficulties of practicing professional activities (63.5%), problems with the Regional Council of Medicine (13%), psychiatric hospital admission (31.2%), and self-medication (71.8%). In our sample, 9.3% of the physicians had changed their area of specialization. CONCLUSIONS: A high prevalence of psychiatric disorders was found in this sample as well as psychosocial and professional problems. Treatment networks focusing on the physicians' mental health could catalyze cultural changes in treatment-seeking behavior, thereby improving early detection and treatment.